The Optimization of the Notary's Role Based on the Value of Justice in Achieving Legal Certainty of Banking Credit - Pertiwi, Desy Artha (Faculty of Law, Universitas Pekalongan, 2024)
Notaries have a moral and professional responsibility to ensure the validity of banking documents and to prevent future disputes. In the context of economic development, the authentic deeds created by notaries play a crucial role in establishing legal order through strong evidence. This research focuses on optimizing the role of notaries in creating justice and legal certainty in the drafting of banking credit deeds. The aim is to examine the role of notaries based on justice values in this process and to provide recommendations for enhancing notaries' responsibilities and legal protection. This study employs a normative research method with a juridical approach, referring to relevant laws and legal literature. The findings indicate that the role of notaries is essential in ensuring the validity of banking credit documents and preventing future disputes. However, ethical challenges and pressures from certain parties often affect this role. The main recommendation of this study is the need for strengthened oversight and improved competence of notaries to support professional integrity and substantive justice in notarial practice.